2018
DOI: 10.4103/jfmpc.jfmpc_301_18
|View full text |Cite
|
Sign up to set email alerts
|

The effect of training problem-based learning on the quality-of-life symptom scales in patients suffering from breast cancer

Abstract: Background and Aim:Breast cancer is one of the most common cancers and most deadly malignancies among the women all over the world. The diagnosis, treatment, and complications arising from this cancer bring about numerous physical, mental, and social complications as well reduced quality of life in these patients. The present study aims at investigating the effect of training problem-based learning on the quality-of-life symptom scales in patients suffering from breast cancer.Materials and Methods:In a randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…As most of the studies in this review were psychoeducational interventions (Ghanbari et al, 2021; Hou et al, 2020; Javadi et al, 2019; Kim et al, 2018; Lepore et al, 2014; Zhu et al, 2018), we infer that nurses have a pivotal role in providing psychological care for women with BC undergoing chemotherapy. As nurses spend more time with patients (Feizi et al, 2018) and provide direct patient care (Melia, 2014), we might infer that they occupy a vantage position in rendering psychological support for patients while chemotherapy is ongoing. Indeed, a qualitative study of women with BC undergoing chemotherapy reported that patients verbalised the need for more support from nurses (Anarado et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…As most of the studies in this review were psychoeducational interventions (Ghanbari et al, 2021; Hou et al, 2020; Javadi et al, 2019; Kim et al, 2018; Lepore et al, 2014; Zhu et al, 2018), we infer that nurses have a pivotal role in providing psychological care for women with BC undergoing chemotherapy. As nurses spend more time with patients (Feizi et al, 2018) and provide direct patient care (Melia, 2014), we might infer that they occupy a vantage position in rendering psychological support for patients while chemotherapy is ongoing. Indeed, a qualitative study of women with BC undergoing chemotherapy reported that patients verbalised the need for more support from nurses (Anarado et al, 2017).…”
Section: Discussionmentioning
confidence: 99%